Access to Scholarly Publications through Consortium in Sri Lanka A Case Study - Wijetunge, Pradeepa (DESIDOC Journal of Library & Information Technology, 2019)
This paper illustrates the complicated process of formulating a library consortium in Sri Lanka, and the process of preliminary activities, selection of databases, awareness raising and training and the later developments are presented as a case study, using appropriate Tables, Figures and textual discussions. Insights are provided to the factors that contributed to the slow but steady establishment and development including the support of the top management of the University Grants Commission, participation of as many academics as possible and the collaborative nature of the implementation process. This is the first ever paper written on the formulation of the Sri Lankan consortium and the publishing will help many researchers to gain firsthand information about its beginnings. Also, the library leaders from other countries where the socio-economic and attitudinal conditions are similar can use the lessons learnt from this initiative for their benefit.